Maternal mortality in the rural Gambia, a qualitative study on access to emergency obstetric care - Sundby Johanne; Cham Mamady; Vangen Siri (BMC, 2005)
Abstract Background Maternal mortality is the vital indicator with the greatest disparity between developed and developing countries. The challenging nature of measuring maternal mortality has made it necessary to perform an action-oriented means of gathering information on where, how and why deaths are occurring; what kinds of action are needed and have been taken. A maternal death review is an in-depth investigation of the causes and circumstances surrounding maternal deaths. The objectives of the present study were to describe the socio-cultural and health service factors associated with maternal deaths in rural Gambia. Methods We reviewed the cases of 42 maternal deaths of women who actually tried to reach or have reached health care services. A verbal autopsy technique was applied for 32 of the cases. Key people who had witnessed any stage during the process leading to death were interviewed. Health care staff who participated in the provision of care to the deceased was also interviewed. All interviews were tape recorded and analyzed by using a grounded theory approach. The standard WHO definition of maternal deaths was used. Results The length of time in delay within each phase of the model was estimated from the moment the woman, her family or health care providers realized that there was a complication until the decision to seeking or implementing care was made. The following items evolved as important: underestimation of the severity of the complication, bad experience with the health care system, delay in reaching an appropriate medical facility, lack of transportation, prolonged transportation, seeking care at more than one medical facility and delay in receiving prompt and appropriate care after reaching the hospital. Conclusion Women do seek access to care for obstetric emergencies, but because of a variety of problems encountered, appropriate care is often delayed. Disorganized health care with lack of prompt response to emergencies is a major factor contributing to a continued high mortality rate.